Molecular Genetics of Liver Neoplasia - Wang, Xin Wei.; Grisham, Joe W.; Thorgeirsson, Snorri S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Cancer is a genetic disease and cancer research is a broad discipline embracing investigators and clinicians with diverse backgrounds. This new edition of Molecular Genetics of Liver Neoplasia intends to provide a comprehensive view on genetics and a mechanistic understanding of liver cancer. The book covers from molecular pathogenesis and cellular origin to translational genomics of liver cancer. The leading experts in the field of liver cancer have thoroughly summarized the latest developments and have provided current viewpoints and novel concepts. This cutting-edge volume is a vital resource for today’s basic cancer researchers, graduate students, medical students and clinicians interested in hepatocarcinogenesis.
Part I: Introduction -- 1. Overview of HCC: biology and pathology -- Xin Wei Wang, Joe Grisham and Snorri Thorgeirsson -- 2. Overview of CC: -- Part II: Liver development and pathogenesis -- 3. Embryonic development of the liver -- Kenneth S. Zaret -- 4. Human hepatic cell lineages -- Nelson Fausto -- 5. Pathology of Human Liver Cancer -- Masamichi Kojiro -- Part III: Genetics and epidemiology of liver cancer -- 6. HCC -- Hashem El.Serag -- 7. CC -- Greg Gores -- Part IV: Molecular Basis of Cancer Susceptibility -- 8. Yusuke Nakamura (NCC) -- 9. Hereditary liver diseases with a high risk to develop HCC -- Markus Grompe, [ALSO Marie-Annick Buendia] -- 10. Genetics and epigenetics of preneoplastic liver diaseses and human HCC -- 11. HBV: Jack Wands -- 12. HCV: Stanly Lemon -- 13. Fibrosis and cirrhosis studies -- David Brenner -- 14. Methylation status in chronic liver disease and HCC -- Yae Kanai (Japan) -- Part V. Animal models -- 15. Transgenic mouse models -- Snorri Thorgeirsson & Joe Grisham -- 16. Mosaic mouse model -- Scott Lowe -- 17. Zebrafish model -- Zhiyuan Gong (NUS): -- Part VI: Global gene expression profiling of human liver cancer -- 18. Integrative and functional genomics of HCC -- Snorri Thorgeirsson: -- 19. Molecular signatures of metastatic HCC -- Xin Wei Wang -- 20. Liver cancer heterogeneity and tumor subtypes -- Jessica Rossi -- 21. Gene expression studies in cholangiocarcinoma -- Yoichi Furokawa -- Part VII: Cancer stem cells -- 22. Snorri Thorgeirsson -- 23. Tania Roskams -- Part VIII: Liver cancer genetics in the clinic -- 24. Biomarkers and clinical staging of liver cancer -- Josep Llovet -- 25. Molecular signaling in HCC -- Hong Yang Wang (Shanghai) -- 26. Molecular oncology and HCC -- Zhao-You Tang (Shanghai) -- 27. Molecular pathogenesis of HCC -- Irene Ig (Hong Kong).
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.